Theoretical Approach of Teaching Written Speech Methodology to The Language University Students (Eurasian Journal of Learning and Academic Teaching, 2022)
The article discusses the process of formation of written communicative competence in the first year of a language university. It describes the construction of a written text based on the analysis of the psycholinguistic features of written speech in English; the principles of constructing a methodology for teaching written speech in the first year of a language university were determined; and also clarified the goals and content of teaching writing in the first year of a language university